Linking Self-Efficacy and Business Ideas to Entrepreneurial Intention: Evidence from Pantawid Pamilyang Pilipino Program (4Ps) Beneficiaries - Talip, Carl Luiz Fiel Alfred; Anugon, Nicole Angeline; Fabria, Williamson; Ocangas, Chris Emmanuel; Solar, Angel Rose; Pagara, Tiffany Jones; Ortega, Sergiris (International Journal of Sustainability and Advanced Integrated Research, 2025)
Entrepreneurship is increasingly recognized as a mechanism for economic empowerment and sustainable livelihood development among marginalized populations. This study, grounded in the Theory of Planned Behavior, investigated the role and link of business self‑efficacy and business ideas in shaping entrepreneurial intention among Pantawid Pamilyang Pilipino Program (4Ps) beneficiaries in Barangay Bonbon, Cagayan de Oro City. Employing a correlational research design and a structured survey, findings revealed that beneficiaries generally demonstrated moderate confidence in their entrepreneurial capabilities, with strong resilience and persistence but weaker competencies in financial management, risk-taking, and strategic decision-making. Their business ideas were well developed, reflecting creativity, motivation, and a strong attitudinal commitment to entrepreneurship, though some expressed reservations about the time demands of self-employment. Business intention was consistently high, characterized by determination, confidence, and readiness to pursue entrepreneurial ventures, albeit with varying perceptions of entrepreneurship as a long-term professional identity. Analysis confirmed significant positive relationships between business self-efficacy and business intention, and between business ideas and business intention, with business ideas exerting the more decisive influence. These results highlight that while beneficiaries possess robust entrepreneurial intention, structural weaknesses in risk tolerance and financial capability may hinder sustainability. The study recommends targeted interventions—such as experiential training, mentorship, business simulations, and cash flow management support — to strengthen self-efficacy and sustain the motivational foundation provided by well-developed business ideas. Such measures are essential for translating entrepreneurial intention into viable, sustainable self-employment outcomes. This study aligns with Sustainable Development Goals (SDGs) 1: No Poverty and 8: Decent Work and Economic Growth by examining entrepreneurship as a mechanism for transitioning 4Ps beneficiaries from conditional aid to sustainable self-employment. The study’s sustainability impact lies in its contribution to socio-economic and community sustainability by informing policy and program designs that integrate entrepreneurship development into social protection initiatives.